Reality Counseling Approach as A Preventive Effort for People with Disabilities - Sri Maullasari (Pamomong: Journal of Islamic Educational Counseling, 2021)
This paper aims to provide a conceptual framework regarding the reality counseling approach as a preventive effort for persons with disabilities. The problems faced by individuals with disabilities are essentially very complex and can be viewed from various aspects. In general, it can be grouped into three, namely learning barriers, developmental delays, and developmental disabilities. To foster a social spirit with disabilities, it is necessary to have facilities that can provide information, namely counseling guidance activities. One effort that can be done is through reality counseling. The concept of reality counseling is to emphasize the responsibility of persons with disabilities in responding to current conditions and to encourage the counselee to face the current reality.